Cycloadditions of Singlet Oxygen for Responsive Fluorescent Polymers - Thomas, Samuel W., III; Altinok, Esra; Zhang, Jingjing (Synlett, 2016)
This account describes progress in the author’s laboratory in the area of new fluorescent polymers that respond to the reactive oxygen species singlet oxygen (1O2). Key to the development of these materials are the [4+2] cycloaddition reactions between singlet oxygen and dienes such as acenes and furans. When covalently bound to conjugated polymer backbones, cycloadditions of these dienes with singlet oxygen can yield dramatic changes in the wavelength and intensity of luminescence: three such examples are given here. The account also summarizes our work to understand how changing the chemical structures of acenes affects reactivity with singlet oxygen as well as the cycloreversion of the resulting endoperoxides.1 Introduction2 Motivation3 Organic Soluble Diene-Linked Conjugated Polymers4 Red-Shifting Woes Lead to Reversibility5 Building a Database6 Integrating Other Acenes7 Conclusion and Looking Forward
Keywords: cycloadditions; singlet oxygen; fluorescence; polymers; acenes